Vitamin B6 Is Required for Full Motility and Virulence in Helicobacter pylori - Alexandra Grubman (American Society for Microbiology, 2010)
ABSTRACT Despite recent advances in our understanding of how Helicobacter pylori causes disease, the factors that allow this pathogen to persist in the stomach have not yet been fully characterized. To identify new virulence factors in H. pylori, we generated low-infectivity variants of a mouse-colonizing H. pylori strain using the classical technique of in vitro attenuation. The resulting variants and their highly infectious progenitor bacteria were then analyzed by global gene expression profiling. The gene expression levels of five open reading frames (ORFs) were significantly reduced in low-infectivity variants, with the most significant changes observed for ORFs HP1583 and HP1582. These ORFs were annotated as encoding homologs of the Escherichia coli vitamin B6 biosynthesis enzymes PdxA and PdxJ. Functional complementation studies with E. coli confirmed H. pylori PdxA and PdxJ to be bona fide homologs of vitamin B6 biosynthesis enzymes. Importantly, H. pylori PdxA was required for optimal growth in vitro and was shown to be essential for chronic colonization in mice. In addition to having a well-known metabolic role, vitamin B6 is necessary for the synthesis of glycosylated flagella and for flagellum-based motility in H. pylori. Thus, for the first time, we identify vitamin B6 biosynthesis enzymes as novel virulence factors in bacteria. Interestingly, pdxA and pdxJ orthologs are present in a number of human pathogens, but not in mammalian cells. We therefore propose that PdxA/J enzymes may represent ideal candidates for therapeutic targets against bacterial pathogens. IMPORTANCE Approximately half of the world’s population is infected with H. pylori, yet how H. pylori bacteria establish chronic infections in human hosts remains elusive. From gene array studies, we identified two genes as representing potentially novel colonization factors for H. pylori. These genes encoded enzymes involved in the synthesis of vitamin B6, an important molecule for many metabolic reactions in living organisms. Little is currently known regarding vitamin B6 biosynthesis in human pathogens. We showed that mutant H. pylori bacteria lacking an enzyme involved in de novo vitamin B6 biosynthesis, PdxA, were unable to synthesize motility appendages (flagella) and were unable to establish chronic colonization in mice. Thus, this work identifies vitamin B6 biosynthesis enzymes as novel virulence factors for bacterial pathogens. Interestingly, a number of human pathogens, but not their mammalian hosts, possess these genes, which suggests that Pdx enzymes may represent ideal candidates for new therapeutic targets.